A novel method based on the Seebeck effect for analyzing the behavior of the PLC band and type A serration. (15th January 2022) - Kwon, Hyeok-Jun; Oh, Seon-Keun; Kim, Hyeong-Dong; Lee, Young-Kook
Abstract: In the present study, a new technique for analyzing dynamic strain aging (DSA), which causes the Portevin-Le Chatelier (PLC) band and type A serrations in a tensile curve, was proposed. The analytical technique is based on the thermoelectric phenomenon known as the Seebeck effect. The variation of the voltage of the gauge part was monitored by the four-wire voltage measurement method during tensile tests. The voltage was additionally changed by a thermo-electromotive force induced by the local deformation heat of the PLC band, i.e. the Seebeck effect. The voltage change led to serrations in the voltage vs. strain (or time) curve. The voltage serrations more clearly exhibited the nucleation and propagation of the PLC band and a critical strain for DSA, which is crucial for investigation of the DSA mechanism, compared to stress serrations in tensile flow curves. Graphical abstract: Graphical abstract Image, graphical abstract